Angiotensin-Converting Enzyme Inhibitor / Angiotensin II Receptor Blocker in COVID-19: a Double-edged Sword or a Myth - Shaha, Kunal Bikram; Adhikari, Ashok; Cho, Jung Rae; Pandey, Bimal; Sharma, Yubaraj; Safi, Sajjad (Nepalese Medical Journal, 2020)
Angiotensin-converting enzyme-2 receptor has been unearthed as a prime site of entry of Severe Acute Respiratory Syndrome Coronavirus 2 owing to its strong affinity towards spike protein of Severe Acute Respiratory Syndrome Coronavirus 2, resulting in down-regulation of Angiotensin-converting enzyme -2 receptors and hyperstimulation of Angiotensin-converting enzyme-1 pathway. This proposed theory has led to the birth of a new controversy regarding the use of Angiotensin-converting enzyme inhibitors/angiotensin receptor blockers in Coronavirus disease 2019 patients. A theory is against the use of Angiotensin-converting enzyme inhibitors/angiotensin receptor blockers, as it enhances the effect of Angiotensin-converting enzyme -2 pathway and upregulation of Angiotensin-converting enzyme -2 receptors resulting in a large number of internalizations of Severe Acute Respiratory Syndrome Coronavirus -2 into cells culminating into a high load of viremia with overwhelming infection and severity. The other theory considers Angiotensin-converting enzyme inhibitors / Angiotensin receptor blockers useful as it blocks deleterious Angiotensin-converting enzyme -1 pathway triggered by Severe Acute Respiratory Syndrome Coronavirus 2 and enhances Angiotensin-converting enzyme -2 receptor upregulation and activation of angiotensin-(1-7) leading to beneficial effects, i.e vasodilation, anti-apoptosis, anti-proliferative, & antifibrosis. Hence, Angiotensin-converting enzyme inhibitors/angiotensin receptor blockers may prove beneficial in countering the Angiotensin-converting enzyme -1 mediated damage by Severe Acute Respiratory Syndrome Coronavirus 2. The recommendations by (European & American) societal guidelines still hold good of not discontinuing Angiotensin-converting enzyme inhibitors/angiotensin receptor blockers in COVID-19 patients as it is further supported by current evidence of large observational studies.